Beyond convergence: climate stress, rural–urban electrification disparities, and agricultural transformation in the east African community - Hersi, Abdifatah Ahmed; Alasow, Ahmed Abdiaziz; Abdi, Yusuf Hared; Ashaari, Zulfa Hanan; Nadarajah, Saralees (Frontiers in Climate, 2025)
This study investigates how climate variability affects rural and urban electricity access differently and how these disparities influence agricultural transformation in the East African Community. Based on a panel dataset covering Kenya, Tanzania, Uganda, Rwanda, and Burundi from 2000 to 2024, we apply climate anomaly analysis, correlation assessment, and performance indexing to explore the links between climate shocks, infrastructure vulnerability, and development outcomes. The results show that rural electricity systems are consistently more sensitive to climate fluctuations than urban ones, with vulnerability indices ranging from 0.234 in Kenya to 1.234 in Burundi. Rather than narrowing, rural–urban electricity gaps widened in most countries, most notably by 23.5 percent in Tanzania and 14 percent in Burundi, while Kenya made substantial progress, reducing its gap by 15.2 percent. Countries with larger electricity access gaps also showed stronger negative correlations between climate variability and agricultural output, including −0.678 in Burundi, highlighting the importance of reliable electricity in reducing climate impacts. In contrast, Kenya’s near-zero correlation suggests that improved electricity access can help buffer agricultural systems from climate stress. These findings highlight a growing adaptation gap, where rural communities, despite facing greater exposure to climate risks, are often the least equipped to respond due to limited access to reliable electricity and enabling infrastructure. The study underscores the need to treat electricity access not only as a development priority but as a vital form of climate adaptation, and calls for spatially targeted, climate-resilient infrastructure strategies to promote equitable and sustainable rural transformation.